Does Adequate Lumbar Segmental Motion Reflect Recovery Process in Acute Lumbar Disc Herniation? - Kim, Hyuntae (Ann Rehabil Med, 2019)
OBJECTIVE: To investigate if the extent of lumbar segmental motion is correlated with the recovery process in the form of pain intensity in patients with acute single level lumbar disc herniation (LDH). METHODS: A retrospective review of medical records was performed on patients presented with acute low back pain from January 2011 to December 2017. With prerequisites of undergoing both lumbar spine magnetic resonance imaging and functional radiography, patients with etiologies other than single level LDH were excluded. A total of 46 patients were selected, including 27 patients with disc herniation at L4-5 level and 19 patients at L5-S1 level. Pearson correlation analysis of pain intensity against segmental range of motion (sROM) and percentage of sROM of each lumbar segment was performed at the initial evaluation point and follow-ups. RESULTS: Serial documentation of pain intensity and functional radiography exhibited an inverse correlation between changes in visual analogue scale (VAS) and sROM in single level LDH at L4-5 level (r=-0.69, p<0.05). In addition, percentage of sROM showed a negative correlation with pain intensity at the aforementioned segment (r=-0.74, p<0.05). Initial pain intensity was also inversely correlated to sROM of the affected segment (r=-0.83, p<0.01 at L4-5; r=-0.82, p<0.05 at L5-S1). CONCLUSION: Improvement in sagittal mobility of the affected segment in LDH adequately reflected mitigation of low back pain during the recovery process. This conjunction could illustrate that the involved segment is overcoming natural immobilization, evidently demonstrating an inverse relationship between initial pain intensity and limitation of sagittal range of motion.